As Mulheres nas redes do tráfico de drogas em Alagoas - Lima, Carla Patrícia Serqueira (2016)
The following abstract analyses female participation in drug trafficking in Alagoas considering the adaptations in the modus operandi of local drug dealers to dodge repression, gender differences in current social panorama, both in the workplace and in relationships, on top of police action in order to restrain female workforce in the State, which mostly takes place in the city outskirts. The current study demonstrates that Brazilian anti-drug policies favours the imprisonment of poor drug dealers while the ones who are more powerful economically and politically are left unpunished. It brings punishment and gender selection into action as well as individual criminal tendencies. Such processes allow police officers to choose whom Justice will target. The research also discusses social and economic aspects of female drug dealers in Alagoas, the male power to which such women are subjected to and their roles in drug trafficking. In order to perform such delicate task, experienced investigators on drug trafficking in state police force were interviewed to gather information about the peculiarities of their action in Alagoas. Furthermore, female inmates at Santa Luzia State Prision, in Maceió were interviewed as to unveil their reasons to participate in such illegal market, the relationships with male drug dealers and their imprisonment circumstances.